2014
DOI: 10.1002/fut.21685
|View full text |Cite
|
Sign up to set email alerts
|

Do Momentum‐Based Trading Strategies Work in the Commodity Futures Markets?

Abstract: This article examines whether momentum-based trading strategies work in the commodity futures markets. Using a wide range of moving average trading rules, commodities are ranked from best-to worst-performing. Then investors are allowed to take long positions in best-performing commodities and a short position in the least attractive commodity. Findings suggest that investors can earn statistically significant profits from the commodity futures markets. Moreover, it is found that short-selling improves commodit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(44 citation statements)
references
References 21 publications
3
40
1
Order By: Relevance
“…Narayan et al [53] found that profits of trading strategies in the commodity futures markets can be frequency-dependent, and Narayan and Sharma [58] also found similar conclusions for spot exchange rate. In order to investigate whether similar conclusions can be drown for oil and natural gas markets, we examine the spillover effects and risk management performance of natural gas and crude oil using US daily and weekly spot price.…”
Section: Alternative Data Frequenciesmentioning
confidence: 75%
See 1 more Smart Citation
“…Narayan et al [53] found that profits of trading strategies in the commodity futures markets can be frequency-dependent, and Narayan and Sharma [58] also found similar conclusions for spot exchange rate. In order to investigate whether similar conclusions can be drown for oil and natural gas markets, we examine the spillover effects and risk management performance of natural gas and crude oil using US daily and weekly spot price.…”
Section: Alternative Data Frequenciesmentioning
confidence: 75%
“…The estimated results of spillover between natural gas and oil prices could be applied to trading strategy by computing the time-varying optimal hedge ratios that minimize overall risk for holding a two-asset portfolio. Narayan et al [53] and Narayan et al [54] studied the profitability of oil markets by trading strategy. Different from them, the aim of trading strategy in this paper is to minimize risk by portfolio management.…”
Section: Model Specificationmentioning
confidence: 99%
“…As a result, the bias does not appear in the forecasts using the AOLS estimator, however, the inefficiency still exists. In response to this, Westerlund and Narayan (2012Narayan ( , 2015a propose a FGLS estimator that accounts for not only the endogeneity and persistency of the predictor variable but also the heteroskedasticity in the predictive regression model. In fact, the results from preliminary analysis show that the aforementioned issues exist in our data sample.…”
Section: Motivation and Contributionmentioning
confidence: 98%
“…That is, the EMH, even in its weaker form (iv'), does not appear to hold in the case of the crude oil market. This result is not at odds with recent empirical evidence that underlines the ine¢ ciency of the futures crude oil market, see, for example, the discussions on this point in Narayan, Huson and Narayan (2012) and Westerlund and Narayan (2013). However, it is worth noting that these authors, using the more restrictive I(0)/I(1) paradigm, reject the hypothesis that the oil spread constitutes a co-integrated relationship.…”
Section: Empirical Analysismentioning
confidence: 69%